Underpinnings of entangled ethnical and gender inequalities in obesity in Cochabamba-Bolivia: an intersectional approach - Yercin Mamani Ortiz; Per E. Gustafsson; Miguel San Sebastián Chasco; Ada Ximena Armaza Céspedes; Jenny Marcela Luizaga López; Daniel Elving Illanes Velarde; Paola A. Mosquera Méndez (BMC, 2019)
Abstract Background Social inequalities in obesity have been observed not only by gender but also between ethnic groups. Evidence on combined dimensions of inequality in health, and specifically including indigenous populations, is however scarce, and presents a particularly daunting challenge for successful prevention and control of obesity in Bolivia, as well as worldwide. Objective The aims of this study were i) to examine intersectional inequalities in obesity and ii) to identify the factors underlying the observed intersectional inequalities. Methods An intersectional approach study was employed, using the information collected in a cross-sectional community-based survey. The sample consisted of youth and adults with permanent residence in Cochabamba department (N = 5758), selected through a multistage sampling technique. An adapted version of the WHO-STEPS survey was used to collect information about Abdominal obesity and risk factors associated. Four intersectional positions were constructed from gender (woman vs. men) and ethnic group (indigenous vs. mestizo). Joint and excess intersectional disparities in obesity were estimated as absolute prevalence differences between binary groups, using binomial regression models. The Oaxaca-Blinder decomposition was applied to estimate the contributions of explanatory factors underlying the observed intersectional disparities, using Oaxaca command in Stata software v15.1. Results The prevalence of abdominal obesity had a higher prevalence in mestizos (men 35.01% and women 30.71%) as compared to indigenous (men 25.38% and women 27.75%). The joint disparity was estimated at 7.26 percentage points higher prevalence in the doubly advantaged mestizo men than in the doubly disadvantaged indigenous women. The gender referent disparity showed that mestizo-women had a higher prevalence than indigenous-women. The ethnic referent disparity showed that mestizo-men had a higher prevalence than indigenous men. The behavioural risk factors were the most important to explain the observed inequalities, while differences in socioeconomic and demographic factors played a less important role. Conclusion Our study illustrates that abdominal obesity is not distributed according to expected patterns of structural disadvantage in the intersectional space of ethnicity and gender in Bolivia. In the Cochabamba case, a high social advantage was related to higher rates of abdominal obesity, as well as the behavioural risk factors associated with them.